A handbook of personnel management practice - Armstrong, Michael (London : Kogan Page, 1977)
The aim of this book is to present an integrated picture of personnel management as a key function in any organization and as a function which concerns all managers. In this second edition, new sections have been included on action learning, advertising, computers in personnel management, do-it-yourself training, negotiating and quality circles.
Includes bibliographical references and index.
ne 12/07/2018
Loans
Keywords: Personnel management